Learning Styles of Non-Science and Technology (S&T) Students on Technical Courses / Noraizan Amran, Farrah Diana Saiful Bahry, Zulkefli Mohd Yusop... [et.al]. - Amran, Noraizan; Saiful Bahry, Farrah Diana; Mohd Yusop, Zulkefli; Abdullah, Szarina (2011)
This study seeks to identify learning styles of students who have little or no background in Science & Technology subjects and are taking technical courses at university level. Understanding students‘ preferred learning styles will help instructors in developing curriculum and teaching techniques to suit students‘ needs. The objectives of the study are: 1. To identify the preferred learning styles of non-Science and Technology (S&T) students on technical courses. 2. To examine the differences in learning styles between male and female students, their academic achievements, and their programs of study. The study poses two research questions: 1. What is the preferred learning style of non-S&T students on technical courses? 2. Are there significant differences in learning styles between the students‘ gender, their programs of studies and the academic achievements of the technical courses? The instrument used to identify students‘ learning styles is Barsch Learning Style Inventory (BLSI) invented by Jeffrey R. Barsch, EdD (1996) which can be easily completed by students. A group of 200 students from Faculty of Information Management, Universiti Teknologi MARA, Malaysia, who registered for the course Database Management System in semester 2009/2010 were invited to take part in the study. They were asked to answer 24 statements in BLSI instrument, at the beginning of the semester. A total of 122 completed responses were used for data analysis using Excel and descriptive statistics. The findings indicate that most students prefer Visual learning style and least number of them prefer Kinesthetic learning style. This result applies to all male and female students in all programs of studies and for different levels of academic achievements. The findings are useful for curriculum designers, instructors, lecturers and policy makers who are involved in one way or others in teaching and learning, and designing the curriculum. Most of all, the students themselves can take appropriate steps to enhance their capability to learn by knowing which learning style best suits their natural preference. Further research should be conducted to more, if not all students, so that more data can be used to further verify the reliability and validity of the Barsch instrument among Malaysian students, and to compare with previous studies from other students in other countries.